2015
DOI: 10.5539/jas.v7n5p124
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Variability and Change on Rainfed Sorghum and Maize: Implications for Food Security Policy in Tanzania

Abstract: Concern about food security has increased because of a changing climate, which poses a great threat to food crop productivity. Climate change projections from the Coupled Model Inter-comparison Project phase 5 (CMIP5) and crop models were used to investigate the impacts of climate change on rain-fed cereal production. Calibrated and evaluated crop models simulated maize and sorghum yields over time periods and scenarios across central zone Tanzania with and without adaptation. Simulation outputs without adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 55 publications
6
25
0
Order By: Relevance
“…In this aspect, the poor have a weak capacity to cope compared to the middle and upper classes. These results of the present study are in agreement with Ahmed et al [4] Below et al [7], Rowhani et al [8], Sieber et al [13], Msongaleli et al [17], and Cooper and Wheeler [22]. Despite little achievement in these adaptation strategies, much more should be done to improve the situation, as proposed by the respondents themselves in Table 4.…”
Section: Discussionsupporting
confidence: 82%
“…In this aspect, the poor have a weak capacity to cope compared to the middle and upper classes. These results of the present study are in agreement with Ahmed et al [4] Below et al [7], Rowhani et al [8], Sieber et al [13], Msongaleli et al [17], and Cooper and Wheeler [22]. Despite little achievement in these adaptation strategies, much more should be done to improve the situation, as proposed by the respondents themselves in Table 4.…”
Section: Discussionsupporting
confidence: 82%
“…They further vetted extreme climate variability as a major cause of the crisis. The studies by Paavola [27] and Msongaleli et al [32] pointed out in favor of the farmers' observation. In addition, the results from interviews cemented on the same.…”
Section: Maize Productionmentioning
confidence: 95%
“…A study by Rowhani et al [25] and Msongaleli et al [32] on the impacts of climate change on cereal crops observed that crop failure is mostly caused by climate variability. They also indicated that, poor people are adversely impacted than the wealthy who are resilient to the dreadful condition.…”
Section: Status Of Food Securitymentioning
confidence: 99%
“…The study region lies between latitudes 5°50′S to 6°10′S and between longitudes 35°40′E to 36°05′E, at an elevation of 1020 m above sea level. The dominant soil of the target region is defined as a ferralic Cambisol (FAO), which is low in fertility and seasonally waterlogged or flooded (Msongaleli et al 2015). Detailed information about the soil used in this assessment is presented in Table 1.…”
Section: Locationmentioning
confidence: 99%